Examining learning difficulties and alternative conceptions students face in learning about hybridization in organic chemistry - Issa I. Salame; David Krauss; Shafic Suleman (International Journal of Chemistry Education Research, 2022)
Chemistry education research has demonstrated that chemistry concepts are abstract, complex, and challenging for students to learn and understand. Chemistry is the branch of science that deals with the nature and behavior of atoms, and bond formation and hybridization both play a crucial role in the discipline. The concept of hybridization deals with the description of the formation of hybrid orbitals, the prediction of bond angles and molecular geometry, and the reactivity of some organic compounds. Development of conceptual understanding of hybridization is important for effective learning about bond formation, molecular structure, bond angle, acidity, and reactivity. This research study aimed to examine alternative conceptions that students hold; the challenges that students face in learning about hybridization; and the strategies that they use to solve hybridization problems. The investigation took place at the City College of New York, an urban, minority-serving institute. Our method of data collection comprised a survey made up of Likert-type, open-ended questions as well as a hybridization-related set of problems. The number of research participants was n = 103. Our research findings suggest that developing conceptual understanding of organic chemistry concepts such hybridization and resonance structures, then relating it to the structure of molecules, is crucial to its function. The presentation of concepts such as hybridization in an oversimplified manner and students’ reliance on memorization in learning can hinder students’ development of conceptual understanding and meaningful learning. Students misestimate their competencies and abilities which can negatively impact poor performers and prevent them from addressing deficiencies in learning about hybridization. We suggest that instructors present the topic of hybridization at the three levels of representations, provide students with opportunities for active learning and knowledge construction, and nurture students’ visualization of atomic and hybrid orbitals. Keywords: science education, alternative conceptions, hybridization, atomic orbitals